(untitled) (Journal of Nepal Geological Society, 2022)
Detailed geological, engineering geological and geotechnical assessment are prerequisites for any design works in underground excavation. Due to complex geology in young Himalayan, it is mandatory. Any misjudgment in support design may results huge losses of cost and time of the project. This paper encompasses detailed analysis carried out for examining the rock mass properties for optimum support along a pressurized headrace tunnel of Upper Balephi “A” Hydroelectric Project, Nepal. Empirical, analytical and numerical methods were applied for safe tunnel design. The rock mass quality and support in these areas were estimated using the rock mass rating (RMR), geological strength index (GSI) and rock mass quality (Q) systems. The detailed rock engineering assessment indicated that there are some critical locations along the headrace tunnel alignment. Rock mass quality values derived from different methods were used for calculating modulus of deformation, Hoek-Brown constants, strength of rock mass, in situ stresses, squeezing and support pressure using available empirical equations. The support determined from the empirical methods were evaluated for the overall stability of the required excavation by using finite element method. The analysis showed that the support pressure and deformation can be predicted very well and magnitude of the displacements and extent of the plastic zones can be reduced significantly by application of the support installation. The numerical modelling reveals that the support suggested by empirical methods are appropriate. Both empirical and numerical approaches are necessary for the confirmation of reliable support design of underground structure.